2006
DOI: 10.1111/j.1464-410x.2006.06628_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐led Flexible Cystoscopy: Experience From One Uk Centre

Abstract: 1 3 2 9 metabolic syndrome. In addition, there is a three-fold increase in the prevalence of LOH and as the number of criteria for the metabolic syndrome increase, as well as the incidence of LOH.Finally, there is a growing body of recent evidence suggesting that metabolic syndrome might be related to other aspects of men's health, including erectile dysfunction, prostate cancer [8] and LUTS. This might pave the way for multi-disciplinary management of these patients, similar to that in urological oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…We are proposing a different methodology that in no way diminishes the UK process. 18 With the optimal components of the tele-cystoscopy found, we will proceed with a pilot study in a telemedicine clinic affiliated with UVA to test the equipment in the field.…”
Section: Discussionmentioning
confidence: 99%
“…We are proposing a different methodology that in no way diminishes the UK process. 18 With the optimal components of the tele-cystoscopy found, we will proceed with a pilot study in a telemedicine clinic affiliated with UVA to test the equipment in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Rattay et al . [8] reported that of 528 FCs performed by nurses, 109 (21%) were referred for a GA cystoscopy. Of these 109, pathology was identified in 98 (90%) and 11 (10%) were normal.…”
Section: Discussionmentioning
confidence: 99%
“…With the pressures of healthcare delivery and increasing workload of urologists, nurse‐led flexible cystoscopy (NLFC) has developed in the UK over the past decade with reports suggesting that adequately trained nurses can undertake FC competently [6]. There have been conflicting reports over the safety and cost‐effectiveness of NLFC [7,8]. We present our initial experience implementing a similar service in a Victorian tertiary hospital and our initial results from analysis of a superficial bladder cancer patient cohort as well from our NLFC service.…”
Section: Introductionmentioning
confidence: 99%